IDENTIFIKASI FAKTOR-FAKTOR KEAMANAN PANGAN· PADA PRODUKSI PUREE JAMBU BIJI MERAH - lndrie Ambarsari; Sarjana Sarjana; Joko Pramono (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2007)
Food safety is conditions and measures to prevent food from possible contamination that can disturb, harm, or make risk for healthy. Pink guavas as one of commodity that developed at Prima Tani's program on Central Java have opportunity to be competitive and certifiable products. One of them is puree. The market demand and customer preference that more selective to a quality and safety products boost a concerning about food safety aspects on each processing steps. This desk study conducted to identify hazard on each processing steps. start form supplying raw materials, food additive utilizing, processing products. packaging, until storage. The right handling steps obtain to reduce the safety risk of products unto the acceptable limit. Risk safety could be come from microbiology, chemical, and physical contaminant. Beside that, there is important to control the employee hygiene and machine sanitation. Quality assurance and food safety handling is the respon• sibility of all stockholders', among producers, trader. customer. and government.